Development of an Instrument to Assess Critical and Creative Thinking Skills in Fourth-Grade Elementary Students - Jufri Saputra; Undang Rosidin; Dwi Yulianti; Mulyanto Widodo (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a higher-order thinking skills-based assessment instrument to measure fourth-grade elementary students’ critical and creative thinking in Science and Social Studies. Using the ADDIE R&D model, the instrument was validated by content, evaluation, and language experts, tested for readability by students, and evaluated for practicality by teachers. Results showed high validity (82%), very good readability (84.58%), and high practicality (93.6%). Student testing indicated stronger performance in critical thinking (interpretation, analysis, evaluation) than in creative thinking (flexibility, fluency, elaboration, originality). The instrument is thus valid, practical, and effective for identifying students' higher-order thinking skills